Presence of citrus tristeza virus (CTV) in Lebanon - D'Onghia A.M.; Khoury W.; Savino V.; Al Bitar L. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
A brief account is given of the presence of CTV in Lebanon, based on surveys in commercial orchards and nurseries. Seventeen out of the 480 samples were tested in ELISA and were found CTV-positive. When indexed to Mexican lime seedlings, all seventeen samples showed vein clearing, leaf cupping and stem pitting symptoms in the indicator plants. No evidence of the disease was observed in the infected trees in the field.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)